Employing oxford nanopore technologies (ONT) for understanding the ecology and transmission dynamics of flaviviruses in mosquitoes (Diptera: Culicidae) from Eastern Colombia (2023)
Studies focused on identifying the viral species of Flavivirus in vectors are scarce in Latin America and particularly in Colombia. Therefore, the frequency of infection of the Flavivirus genus and its feeding preferences were identified in the mosquito species circulating in the municipality of Puerto Carreño-Vichada, located in the Eastern Plains of Colombia. This was done by sequencing the viral NS5 and vertebrate 12S rRNA genes, respectively, using Oxford Nanopore Technologies (ONT). A total of 1,159 mosquitoes were captured, with the most abundant species being Aedes serratus at 73.6% (n = 853). All the mosquitoes were processed in 230 pools (2–6 individuals) and 51 individuals, where 37.01% (n = 104) were found to be infected with Flavivirus. In these samples, infection by arboviruses of epidemiological importance, such as dengue virus (DENV), Zika virus (ZIKV), and chikungunya virus (CHIKV), was ruled out by PCR. However, through sequencing, infection by different insect-specific viruses (ISFVs) and a medically important virus, West Nile virus (WNV), were identified in a mosquito of the Culex browni species. Additionally, the feeding patterns showed that most species present a generalist behavior. Given the above, conducting entomovirological surveillance studies is crucial, especially in areas of low anthropogenic intervention, due to the high probability that potentially pathogenic viruses could generate spillover events under deforestation scenarios.